Study on Using Polymerase Chain Reaction and Buffy Coat Smear Method for Trypanosoma evansi Detection in Buffalos of Eastern Thailand - Panja, Kamonporn; Sananmuang, Thanida; Jankong, Thanakrit (Journal of Mahanakorn Veterinary Medicine, 2018)
The objective of this study was to study on using polymerase chain reaction (PCR) and Buffy coat smear method for Trypanosoma evansi detection in buffalos of eastern Thailand. Samples were collected from buffalo blood during July - December 2016. There were 80 samples; 40 samples from Chachoengsao province and the others were collected from Sa Kaeo province. All the samples were tested by PCR and buffy coat smear method. Packed cell volume (PCV) and plasma protein (PP) of samples were measured and data of husbandry management in each farm were recorded. Results from this study revealed that there was no T. evansi infection in sample from Sa Kaeo province. But, two infected samples of Chachoengsao province were found by both PCR and Buffy coat smear method. Therefore, PCR and buffy coat smear method had 100% sensitivity and 100 % specificity. The prevalence of all samples was 2.5% (2/80). Prevalence of Chachoengsao province was 5% (2/40) while the disease was not detected in Sa Kaeo province. Analysis of husbandry management showed that all of farmers in Chachoengsao and 80 % of farmers in Sa Kaeo province province raise buffalos with other animals. In addition, vector insects were found in almost all buffalos (78/80). The average PCV of samples in Sa Kaeo province (33±2 %) were more than those of Chachoengsao province (29±5 %).The average PP of Chachoengsao province (9.2±0.8 g/dL) were more than Sa Kaeo province (8.8±0.8 g/dL). However,data of husbandry management, vector insects, PCV and PP did not relate to found T. evansi infection in buffalos